THE IMPROVEMENT AREAS OF SOCIAL PEDAGOGICAL ASSISTANCE PROVIDED TO PUPILS WITH EMOTIONAL AND BEHAVIOURAL DISORDERS - Šmitienė, Gražina; Klaniene, Ilona (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The article reveals problems and weaknesses of social pedagogical assistance provided to pupils with emotional and behavioural disorders (EBD) and provides insights into the development of social and educational support at schools. The qualitative research (focus group and interviews), in which there participated social workers and teachers (two groups of informants), has been conducted. The content analysis of the research findings has revealed the major weaknesses of assistance provided to pupils with EBD and its improvement areas: lack of professionals providing necessary help at schools, lack of teachers' special professional competences (the ability to recognize EBD problems, knowledge and skills of providing assistance), lack of cooperation between child assistance specialists, teachers, and parents (feedback problems), and a lack of motivation.